The Invisible Collateral - Silu Muduli; Shridhar Kumar Dash (Economic and Political Weekly, 2019)
A borrower may hesitate to borrow from her close relatives and family members as it costs them in terms of reduction in social insurance in the case of default. This invisible cost reduces credit risk. India's household indebtedness survey shows some evidence on these borrowing preferences. This perspective on borrowing decisions derived from the community can be used as one of the dimensions in credit risk evaluation and in policy formulation.
Keywords: 330; Network; Trust; Credit Risk